TRADITION AND INNOVATION: THEORETICAL BASIS, IMPROVEMENT AND TYPES (Scientific journal of the Fergana State University, 2025)
This article reflects the scientific and theoretical views of our literary scholars on tradition and innovation, as well as the theoretical foundations of tradition and innovation in the field of literary studies. Tradition has been studied in literary studies since ancient times. Their scientific and theoretical views on literary tradition are analyzed using examples. The specific features of the tradition of using artistic words are shown. The cultural and spiritual forms of literary tradition are scientifically illuminated. In addition, scientific views on the role of innovation, which is always in dialectical contact with tradition, in the work of poets and its features in fiction are analyzed. Tradition and innovation occupy a key place in the formation of literature. We observe mutual proximity in the scientific views of ancient scholars on tradition and innovation.